Multidimensional Business Feasibility and Strategic Capability Priorities in a Traditional Food Agroindustry: A DSS-Based Case Study of Suwar-Suwir in Jember, Indonesia - Al Gore Alfarizi (CV. SPDFHarmony, 2026)
Background: Traditional food agroindustries may possess strong product identity while remaining vulnerable to fragmented marketing, semi-modern production, informal financial recording, and weak integration across business functions. Aims: This study evaluates the multidimensional feasibility of UD. Sari Rasa, a suwar-suwir agroindustry in Jember, Indonesia, and develops transparent strategic capability priorities from its Decision Support System (DSS) outputs. Methods: A descriptive quantitative single-case design used DSS-UMKM version 2.0 to assess legal, marketing, production, management and human resources, business environment, and financial dimensions. Primary evidence came from the owner-manager through questionnaires, structured and unstructured interviews, and observation, while company records supported business and financial verification. The analysis retained the original 2021–2022 study period, a 10-year projection horizon, and a 15% discount rate. Results: Management and human resources showed high feasibility (12/15), whereas marketing (60/80), production (37/50), and business environment (19/24) were classified as moderately feasible. Legal documents recorded in the study period included NPWP, SIUP, and PIRT. Financial outputs indicated feasibility, with a break-even quantity of 5,439.09 units, break-even sales of IDR 181,332,672.91, BCR of 7.23, payback period of 2.28 years, NPV of IDR 5,649,026,135.05, profitability index of 53.06, and IRR of 59.20%. Conclusion: The enterprise was financially viable, but its development potential depended on closing capability gaps in digital market activation, production standardization, financial recordkeeping, and periodic compliance review. The study contributes a cross-dimensional interpretation that treats financial feasibility as a resource base for capability upgrading rather than as evidence that current practices should remain unchanged.